New perspectives in interactional linguistic research - Selting, Margret; Barth-Weingarten, Dagmar (Studies in language and social interaction, 2024)
This collection of original papers illustrates recent trends and new perspectives for future research in Interactional Linguistics (IL). Since the research program was started around the turn of the century, it has prospered internationally. Recently, however, new developments have opened up new perspectives for interactional linguistic research. IL continues to study the details of talk in social interaction, with a focus on linguistic resources and structures of verbal and vocal interaction in bodily-visible interactional settings. Increasingly, though, it embraces methods supported by new technology and broadens its data and research questions to applications in teaching, therapy, etc. The volume comprises three parts with 14 contributions: (1) Studying linguistic resources in social interaction; (2) Studying linguistic resources in embodied social interaction; and (3) Studying social interaction in institutional contexts and involving speakers with specific proficiencies.
Keywords: Kommunikationsanalyse; Interaktion; Soziolinguistik